การติดเชื้อไวรัสตับอักเสบ ซี ในผู้ป่วยไลเคนพลานัสในช่องปาก - ปรมาภรณ์ กลั่นฤทธิ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
For the last two decades, several studies have been conducted focusing on an association between hepatitis C virus infection and lichen planus (LP). Not all of those studies have found an association between both kinds of disease. Differences as to the patients geographical location could be an important factor for HCV prevalence. The present study has been designed to investigate the prevalence of HCV infection based on the presence of anti-HCV and/or HCV-RNA in 60 patients with oral lichen planus (OLP) and 60 controls without OLP, matched by age and gender. We found 5 patients (8.33%) with OLP infected with HCV : 3 patients were positive for both anti-HCV and HCV-RNA, 1 patient was positive for anti-HCV only, and 1 patient was positive for HCV-RNA only, whereas all the controls were negative for both anti-HCV and HCV-RNA. Thus, the present study suggests a small but statistically significant high prevalence of HCV infection in patients with OLP although the underlying mechanism still remains unknown. Further studies should be investigated in the mechanism of this association.